Topicality of John Paul II’s Pedagogical Message - Alina Rynio (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The purpose of this study is to outline the sources and aspects of the time- surpassing topicality of the Pope’s vision of integral education apparent in his anthropological, permeated with faith, reflection on man. In his vision, the internal perception conditions the integral education of man. The research confirms the thesis that the Pope’s pedagogy assumes an “adequate anthropology” and opens the human heart to the objective order of truth, including truth about Christ as “the centre of the universe and of history” (Redemptor hominis, 1) and to the fundamental truth about man. The Pope’s pedagogy with its anthropological grounding is topical due to the fact that it offers, contemporary times permitting, a complete vision of human education. This vision goes against the culture of lost faith, dehumanisation, nihilism, and existential cynicism, and also against axiological relativism. In this vision, science, technology, art, peace, justice, God, true religion, nature, grace, faith, hope and love are not in complementary distribution, but complement each other. The timeless source of the topical quality of the Pope’s pedagogical message appears to reside in the compatibility and completeness of the human image it provides. It investigates the complex matter of education and the individual story of shaping personalities of outstanding individuals. With due respect and unanticipated amazement, it also provides an outline of the Catholic interpretation of education and the human condition.